Efficiency of Molecular Diversity vs Phenotypic Diversity in Attaining Heterosis -A Case Study with Tomato - Bhandari, Hem Raj; Srivastava, Kartikeya; Biswas, Subrata; Tripathi, Manoj Kumar; Chaudhary, Babita (International Journal of Bio-resource and Stress Management, 2019)
Presently, both the traditional (phenotypic diversity) and modern tools (molecular markers) are being used to select diverse parents in crop improvement programmes. Several reports are available detailing parallelism between these two types of diversity. However, reports on comparative efficiency of these two types of diversity in terms of attainment of heterosis are lacking. In this context, present investigation was carried out to compare the efficiency of phenotypic diversity vs molecular diversity in realizing genetic components (general combining ability effect, specific combining ability effect and heterosis) determining hybrid performances in tomato. Sixty six tomato entries were subjected to phenotypic- and molecular-diversity assessment using nine phenotypic traits and 29 SSR markers, respectively. Accordingly, two sets of dendrograms were developed. One genotype from each cluster of two dendrograms was selected separately, crossed in half diallel fashion and evaluated in three diverse regions of India. ‘Desirability quotient’ was calculated for general combining ability effect among two set of parents, and for specific combining ability effect and commercial heterosis among two sets of crosses for important yield traits. Desirability quotient was calculated based on mean desirable genetic parameters (GCA effect, SCA effect and commercial heterosis) and proportion of parents depicting desirable genetic parameters. Molecular diversity-based crosses possessed higher desirability quotient of specific combining ability effect and desirability quotient of heterosis for yield traits under study. The study revealed efficiency of molecular markers in comparison to phenotypic traits in identifying diverse groups possessing higher non-additive gene action and ultimately leading to higher heterosis in tomato.